Toxocariosis and inflammatory joint disease (Gaceta de Ciencias Veterinarias, 2017)
Toxocariosis is a serious epidemiological problem in many countries; it is a zoonotic disease, humans can become infected by ingestion of Toxocara canis infective eggs, which are found in contaminated soil with canine feces. Diagnosis in humans is complicated, so it is not really taken in consideration as a differential diagnosis in diseases human; however, the presence of this parasitosis has been associated with some chronic inflammatory diseases such as atopy, asthma and arthritis. Hence the importance of analyzing the toxocariosis and its relationship with joint inflammatory disease in humans; since besides, exist two types of arthritis whose severity has been associated with the presence of Toxocara canis: rheumatoid arthritis and ankylosing spondylitis, which could be attributed to that this parasite induces constant secretion of a cytokine called interleukin-33, which has proinflammatory effects by activating mast cells, inducing a process of injury synovial membrane impacting joint progressively. It would be interesting to include toxocariosis, among the possible causes that generate or increase the severity of arthritis, in order to lead implementation of an appropriate treatment in these patients to allow their successful recovery.
Keywords: Toxocara canis; arthritis; zoonotic disease; synovial membrane; interleukin; mast cell